HSPA1A conformational mutants reveal a conserved structural unit in Hsp70 proteins - Vandova, Veronika; Vankova, Pavla; Durech, Michal; Houser, Josef; Kavan, Daniel; Man, Petr; Muller, Petr; Trcka, Filip (Biochimica et biophysica acta. G, General subjects, 2020)
BACKGROUND: The Hsp70 proteins maintain proteome integrity through the capacity of their nucleotide- and substrate-binding domains (NBD and SBD) to allosterically regulate substrate affinity in a nucleotide-dependent manner. Crystallographic studies showed that Hsp70 allostery relies on formation of contacts between ATP-bound NBD and an interdomain linker, accompanied by SBD subdomains docking onto distinct sites of the NBD leading to substrate release. However, the mechanics of ATP-induced SBD subdomains detachment is largely unknown. METHODS: Here, we investigated the structural and allosteric properties of human HSPA1A using hydrogen/deuterium exchange mass spectrometry, ATPase assays, surface plasmon resonance and fluorescence polarization-based substrate binding assays. RESULTS: Analysis of HSPA1A proteins bearing mutations at the interface of SBD subdomains close to the interdomain linker (amino acids L399, L510, I515, and D529) revealed that this region forms a folding unit stabilizing the structure of both SBD subdomains in the nucleotide-free state. The introduced mutations modulate HSPA1A allostery as they localize to the NBD-SBD interfaces in the ATP-bound protein. CONCLUSIONS: These findings show that residues forming the hydrophobic structural unit stabilizing the SBD structure are relocated during ATP-activated detachment of the SBD subdomains to different NBD-SBD docking interfaces enabling HSPA1A allostery. GENERAL SIGNIFICANCE: Mutation-induced perturbations tuned HSPA1A sensitivity to peptide/protein substrates and to Hsp40 in a way that is common for other Hsp70 proteins. Our results provide an insight into structural rearrangements in the SBD of Hsp70 proteins and highlight HSPA1A-specific allostery features, which is a prerequisite for selective targeting in Hsp-related pathologies.
Keywords: konformace proteinů; Protein Domains; Humans; Mutation; vodík-deuteriová výměna; mutace; Deuterium Exchange Measurement; HSP70 Heat-Shock Proteins; Protein Binding; adenosintrifosfát; vazebná místa; Binding Sites; Adenosine Triphosphate; Allosteric Regulation; vazba proteinů; Protein Conformation; alosterická regulace; lidé; proteinové domény; proteiny tepelného šoku HSP70